Exploring the Transformative Role of Micro Credit Services in Advancing Economic and Social Empowerment among Women through Self-Help Groups in the Banking Sector Context - S.D. Vashanth; Dr. C. Sengottuvel (IJRDO - Journal of Business Management, 2025)
The study examines the impact of micro credit initiatives of the banking sector on women’s empowerment through the functioning of Self-Help Groups (SHGs). A quantitative research design was employed, using primary data collected from SHG members in Salem district. Empowerment was analysed across three dimensions—economic, social, and psychological—using MANOVA, hierarchical regression, and cluster analysis. MANOVA results revealed significant multivariate differences across empowerment dimensions based on the level of micro credit initiatives, with higher credit quality associated with stronger empowerment outcomes. Hierarchical regression established that micro credit initiatives exert a direct positive influence on empowerment, while SHG functioning plays a strong independent role. The decline in the MCI coefficient after including SHG functioning indicates partial mediation, suggesting that credit design indirectly enhances empowerment by strengthening group processes. Cluster analysis identified three distinct segments: high-design high-outcome groups, under-served but cohesive groups, and design-constrained groups, each displaying different empowerment profiles. These findings highlight that credit design alone is not sufficient to produce broad-based empowerment gains. Effective empowerment emerges when flexible financial products are combined with robust group functioning. Policy implications include designing adaptive loan terms, investing in SHG capacity building, and instituting targeted monitoring frameworks to address heterogeneity among groups. The integrated analytical approach demonstrates how financial and institutional mechanisms can jointly advance women’s empowerment in rural credit ecosystems.